Tell me what type of extracellular vesicles you secrete, and I will tell you who you are: yeast or hypha. Issue 12 (17th December 2021) - Martínez-López, Raquel; Vaz, Catarina; Redondo, Esther; Calvo, Guillermo; Hernáez, María Luisa; Gil, Concha; Monteoliva, Lucía
Abstract : The transition between yeast and hyphal morphologies plays a crucial role in the pathogenicity of Candida albicans . Recent studies have pointed out the great relevance of extracellular vesicles (EVs) secreted by microorganisms in a wide variety of biological processes including interaction with the host. Therefore, the main objective of this work was to compare the EVs secreted by yeast and hyphal forms to shed light on C. albicans -host interaction. EVs were obtained by ultracentrifugation of the culture medium supernatant and analysed by mass spectrometry. They were characterized by transmission electronic microscopy (TEM) and dynamic light scattering (DLS). DLS and TEM analysis showed that yeast EVs were significantly bigger than hyphal EVs, being most of them in the range between 400 to 500nm while hyphal EVs were ranged mostly around 100-200nm. Proteomic analysis showed greater protein diversity in hyphal EVs when compared to yeast EVs (up to 1700 different proteins identified versus 300), although less amount of total protein was obtained. Gene Ontology (GO) analysis showed that yeast EVs were enriched in surface proteins while hyphal EVs, although containing also most of these surface proteins, were also significantly and exclusively enriched in proteins involved in protein metabolism (ribosomal proteins, many aminoacid-pathway enzymes and proteasome) and cellular transport. The differences between YEVs and HEVs also prompted a different immune host response, as tested with macrophage cell cultures and human sera from patients with invasive candidiasis. All these differences point out a possible different biogenesis and roles of EVs secreted by both morphologies.